DRUG-ELUTING STENTS OUTCOMES IN DIABETICS WITH CORONARY ARTERY DISEASE AND PULMONARY IMPLICATIONS - SHEHZAD , ST; FARRUKH , S; AFNAN , M; YOUSUF , MH (Biological and Clinical Sciences Research Journal, 2023)
The study aims to investigate the outcomes of drug-eluting stents (DES) in patients with diabetes mellitus and coronary artery disease (CAD) while considering implications for pulmonary and cardiac health. A prospective observational study design was employed. A cohort of 54 patients who underwent percutaneous coronary intervention (PCI) with DES implantation was included. Primary outcome measures included stent patency rates, restenosis rates, major adverse cardiovascular events (MACE), and pulmonary function tests. Subgroup analyses were conducted based on age and gender. The study unveiled a 91.5% stent patency rate at six months and a 12.3% restenosis rate. Furthermore, the cumulative MACE incidence at one year was 18.5%. Subgroup analysis identified gender-based differences in restenosis rates and a slightly elevated MACE incidence among patients with longer diabetes duration. Importantly, pulmonary function tests, encompassing spirometer and lung volume assessments, demonstrated no significant pulmonary impairment following DES implantation. These assessments indicated only a marginal 1.2% reduction in FEV1, while TLC remained statistically unchanged, reassuring that DES utilization does not adversely impact pulmonary health. This study contributes to the growing body of evidence supporting the use of DES as a viable intervention in managing CAD in diabetic patients with potential implications for both cardiac and pulmonary health. The outcomes highlight DES's potential to enhance long-term cardiovascular effects in this high-risk population.